On reading books to children parents and teachers - Van Kleeck, Anne; Stahl, Steven A.; Bauer, Eurydice Bouchereau (L. Erlbaum Associates, 2003)
On Reading Books to Children: Parents and Teachers brings together in one volume current research on adult book reading to children. The authors, drawn from around the world, are key researchers and eminent scholars from the fields of reading.